Adequacy of quality provision in standard forms of local and international construction contracts. - Kwang, Q.W; Ting, S.N (Universiti Malaysia Sarawak (UNIMAS), 2009)
This paper presents a study of various quality related clauses in local and international standard forms and comparisons were made among the chosen forms. Experts opinion within this field are sought as well in order to improve the robustness of this study. This paper also investigates the adequacy of the provision of these forms and suggests suitable changes to the current standard forms, where necessary, within the study.